Charakter spółek notowanych na rynku NewConnect - Domaradzki, Paweł (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The purpose of the article is to present the real character of companies listed on the alternative financial market in Poland. The adopted research hypothesis assumes, that mainly young, innovative and fast-growing companies are listed on the NewConnect market.. The empirical analysis showed that most of the business units listed on the NewConnect market, unfortunately, do not develop rapidly. They are also characterized by having a short period between their establishment and entering the financial market and an innovative character. It has also been proven that there are Polish companies listed on the market that come from branches of industry whose level of innovation, due to the character of their operations, isn’t a key element of their functioning. What is more, the conducted research has shown that the changes taking place on the NewConnect market (since the moment of its founding to date) are unfortunately not favorable. At the beginning of the functioning of the alternative financial market in Poland, the companies listed on it had a relatively high level of innovation, unfortunately, the current level of this phenomenon has decreased.